Evolving Concepts of Epistemic Injustice - Fricker, Miranda (Las Torres de Lucca. International Journal of Political Philosophy, 2021)
This text is the Spanish translation of the fourth chapter of The Routledge Handbook of Epistemic Injustice (2017), edited by Ian James Kidd, José Medina and Gaile Pohlhaus Jr. In it, Miranda Fricker clarifies and circumscribes the concepts of hermeneutic and testimonial injustice, by providing examples, explaining their genealogy, answering to some of the criticism that these concepts have received and establishing similarities and contrasts with other conceptualizations of justice and some other branches of philosophy, as well
Keywords: epistemic injustice; testimonial injustice; discrimination; intentionality; healthcare philosophy; standpoint